Dual antiplatelet therapy reduced stroke risk in high‐risk patients with transient ischaemic attack assessed by ABCD3‐I score. (17th December 2018) - Song, B.; Hu, R.; Pei, L.; Cao, Y.; Chen, P.; Sun, S.; Wang, X.; Tian, X.; Guo, Y.; Xu, Y.
Abstract : Background and purpose: Several clinical trials have demonstrated that dual antiplatelet therapy (DAPT) benefited patients with transient ischaemic attack (TIA) with an ABCD2 score ≥4. The present study aimed to investigate whether the ABCD3‐I score could be a more appropriate tool for selection of patients with TIA to receive DAPT in real‐world settings. Methods: We derived data from the TIA database of The First Affiliated Hospital of Zhengzhou University. The predictive outcome was ischaemic stroke at 90 days. The additive interaction effect was presented by the attributable proportion due to interaction. Kaplan–Meier curves were plotted to present cumulative stroke rates in different risk categories with monotherapy and DAPT. Cox proportional hazards regression was used to determine risk factors associated with stroke. Results: Among 785 patients, the mean (SD) age was 56.95 (12.73) years and 77 patients (9.8%) had an ischaemic stroke at 90 days. A total of 55.8% of patients (attributable proportion due to interaction; 95% confidence interval, 20.8%–90.9%) were attributed to additive interaction of ABCD3‐I score and antiplatelet therapy. Kaplan–Meier curves showed a significant difference between patients receiving monotherapy and DAPT in high‐risk patients with TIA ( P = 0.021). DAPT reduced 90‐day stroke risk in high‐risk patients with TIA as assessed independently by ABCD3‐I score (adjusted hazard ratio, 0.43; 95% confidence interval, 0.20–0.92, P = 0.031). The benefit did not exist in low‐ and medium‐risk patients by ABCD3‐I score (patients with ABCD2 score ≥ 4 or <4). Conclusions: High‐risk patients with TIA assessed by ABCD3‐I score received the most pronounced clinical benefit from early use of DAPT in real‐world clinical experience.